2018
DOI: 10.1111/ggi.13571
|View full text |Cite
|
Sign up to set email alerts
|

Associations of social frailty with loss of muscle mass and muscle weakness among community‐dwelling older adults

Abstract: Aim The present cross‐sectional study examined the associations of social frailty status with loss of muscle mass and weakness among community‐dwelling older adults. Methods Data from 353 older adults (74.8% women) who had participated in a community‐based health check survey (Tarumizu Study) were analyzed. Social frailty was defined using responses to five questions (going out less frequently, rarely visiting friends, feeling unhelpful to friends or family, living alone and not talking with someone every day)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 30 publications
1
46
1
Order By: Relevance
“…But Williams et al 31 only found a weak association between muscle mass and frailty in the sample of elder adults with cancer. Makizako et al 32 found that social frailty was not independently associated with loss of skeletal muscle mass after adjusting for covariates. In the present study, skeletal muscle mass in frail inpatients was less than that in non-frail inpatients.…”
Section: Discussionmentioning
confidence: 97%
“…But Williams et al 31 only found a weak association between muscle mass and frailty in the sample of elder adults with cancer. Makizako et al 32 found that social frailty was not independently associated with loss of skeletal muscle mass after adjusting for covariates. In the present study, skeletal muscle mass in frail inpatients was less than that in non-frail inpatients.…”
Section: Discussionmentioning
confidence: 97%
“…This questionnaire was originally derived from the data of community‐dwelling elderly adults (≥65 years), and social frailty, as defined by this questionnaire, is associated with future disability 13 . Moreover, it relates to a significantly higher incidence of muscle weakness 14 and onset of depressive symptoms 15 in community‐dwelling adults aged ≥65 years. The original paper defined two or more criteria for positive responses as indicating social frailty; the present study used the same criteria for consistency.…”
Section: Methodsmentioning
confidence: 99%
“…In 2017, the National Center for Geriatrics and Gerontology launched the ''Integrated Longitudinal Studies on Aging in Japan'' (ILSA-J) with the collaboration of 13 longitudinal cohort studies on aging conducted in older people living in the community. [4][5][6][7][8][9][10][11][12][13][14][15][16] The cohorts identified for this research were considered to be representative of the Japanese older population and have relatively high accuracy. The cohort studies included in ILSA-J satisfied the following criteria: being conducted in Japan, including Japanese older adults 65 years of age and above living in the community, observational study on aging using standardized methods of measurement, and has published the study design.…”
Section: About Integrated Longitudinal Studies On Aging In Japanmentioning
confidence: 99%